@Wolgwang Oh I forgot to talk about your question? But replacing every + with a \vee and . with a \wedge should do your job. Actually, there's no problem I see with an expression like 1 \wedge v or something , but to eliminate the 1, you just need to use the fact that 1.a = a for all a and 1+b = 1 for all b. If you use that, you get rid of the 1s, and then you can put the \wedge and \vee in place.
It's just a change of notation, so it can always be done.
Attempting this for that expressions gives me : X \vee (X \wedge Y) \vee (X \wedge Z) \vee (Y \wedge Z) = [X \wedge (1 \vee Y)] \vee (X \wedge Z) \vee (Y \wedge Z)
There's also another thing the author missed, which could have simplified a step.
Indeed, we have $X+XY+XZ+YZ$. Instead of going with just removing X from X+XY, (s)he could have written X(1+Y+Z)+YZ and used the laws 1+A =A and 1.B = B to directly get X+YZ.